Revitalisasi Kesejahteraan Sosial Bertetangga Perspektif KH. Muhammad Romzi Al-Amiri Mannan: Studi Kitab Umdatul Mukhtar ‘Ala Mabahisi Huquqi Al-Jari - Kholilah, Kholilah (Mahad Aly Al Fithrah Press, 2022)
Today social problems come back in the main spotlight in this country, especially during the pandemic hasn’t a meeting point. Since pandemic Covid-19, it has officially entered the motherland. Social problems are increasing, especially in economic problems. This leads to reduced welfare of people's lives and creates social inequalities, especially in smaller domains such as resilience. The results of this study revealed that there are three points conceptualized by Ajengan Romzi in fulfilling neighborly matters. First, there are consequences that are obtained when treating neighbors badly. Second, treating neighbors well will also reduce social problems among neighbors and can also eliminate gaps that occur. Third, a good form of interaction with neighbors, as well as how to deal with neighbors who treat us badly, should not only be applied not only with neighbors who are fellow Muslims but also neighbors who are non-Muslims.